Implementation of Zakat Law in Empowering the Islamic Community's Economy in Indonesia - Judijanto, Loso (The Easta Journal Law and Human Rights, 2024)
This research investigates the implementation of Zakat law in Indonesia and its implications for empowering the Islamic community's economy. Zakat, an obligatory form of almsgiving in Islam, holds significant importance in Islamic finance and social welfare systems. The study utilizes qualitative research methods, including interviews, focus groups, and content analysis, to explore the challenges and opportunities in implementing Zakat law and its impact on economic empowerment. Key findings highlight the importance of governance, transparency, and accountability in Zakat administration, as well as the role of Zakat in poverty alleviation, livelihood enhancement, and community development. The study provides actionable recommendations for enhancing the effectiveness of Zakat administration and promoting sustainable economic development within the Islamic framework in Indonesia.